Observaciones sobre la peregrinación islámica delegada en los trabajos de Chardin, Niebuhr y Burckhardt (siglos XVII-XIX) - Carro Martín, Sergio (El Colegio de México, 2021)
Records exist of Islamic pilgrimages by proxy since the beginning of the eleventh century thanks to the advent of a new typology of documents: pilgrimage certificates. However, and despite documentation in the main Sunnī and Shi‘ī legal works, there are still gaps in the sources that could help explain the bureaucracy that developed around this form of pilgrimage, especially between the seventeenth and nineteenth centuries. Conversely, three European travelers—Jean Chardin, Carsten Niebuhr, and Johann Ludwig Burckhardt—provide valuable information about pilgrimages by proxy overlooked by previous studies on Islamic pilgrimages. This article explores this form of pilgrimage and the issuance of certificates by analyzing different extracts from the works of these three travelers.